Patient Reported Outcomes in Cancer Survivorship - Ballard, Sheri (My University, 2020)
Background: Survivorship services and the use of the treatment summary and survivorship care plan (SCP) have been in place for over ten years. This project evaluates the impact and efficacy of a general survivorship clinic at a comprehensive cancer center by utilizing patient reported outcome data collected pre- and post-clinic combined with medical record derived demographic and treatment data. Methods: The key outcomes measured in this longitudinal study include pre-clinic to one year post-clinic change in knowledge of survivorship information (diagnosis, treatment and long term effects), cancer and treatment related distress (uncertainty, family strain, medical demands, finances, identity, health burden and interference) and health-related quality of life (physical, emotional and social functioning, pain, general health and vitality) as well as the extent to which the clinic visit and SCP met patient needs. The population is described in detail including demographics, diagnosis and treatment history (N=219). Results: Patient knowledge of their own diagnosis and treatment history as well as of the long term effects of their cancer treatment increased after the clinic visit. Overall treatment related distress decreased in addition to distress in the areas of uncertainty and family strain. Over 90% of patients found the SCP useful and reported that the clinic visit met their needs in all areas surveyed including practical, resource, emotional, and symptom-related needs. Conclusions: Although the changes were small, findings from this study support the use of a dedicated, general survivorship clinic model for cancer survivors. This model may be a feasible approach to ensuring our already overtaxed healthcare system can meet the myriad needs of the growing population of cancer survivors.
Thesis (Master's)--University of Washington, 2020
Keywords: cancer; patient reported outcomes; survivorship; survivorship clinic; Oncology; Public health; Health services